Phase Evolution of Re1-xMoxSe2 Alloy Nanosheets and Their Enhanced Catalytic Activity toward Hydrogen Evolution Reaction - Kwak, In Hye; Kwon, Ik Seon; Debela, Tekalign Terfa; Abbas, Hafiz Ghulam; Park, Yun Chang; Seo, Jaemin; Ahn, Jae-Pyoung; Lee, Jong Hyun; Park, Jeunghee; Kang, Hong Seok (AMER CHEMICAL SOC, 2020)
Two-dimensional ReSe2 has emerged as a promising electrocatalyst for the hydrogen evolution reaction (HER), but its catalytic activity needs to be further improved. Herein, we synthesized Re1-xMoxSe2 alloy nanosheets with the whole range of x (0-100%) using a hydrothermal reaction. The phase evolved in the order of 1T '' (triclinic) -> 1T' (monoclinic) -> 2H (hexagonal) upon increasing x. In the nanosheets with x = 10%, the substitutional Mo atoms tended to aggregate in the 1T '' ReSe2 phase with Se vacancies. The incorporation of the IT' phase makes the alloy nanosheets more metallic than the end compositions. The 10% Mo substitution significantly enhanced the electrocatalytic performance toward HER (in 0.5 M H2SO4), with a current of 10 mA cm(-2) at an overpotential of 77 mV (vs RHE) and a Tafel slope of 42 mV dec(-1). First-principles calculations of the three phases (IT '', 2H, and IT') predicted a phase transition of 1T ''-2H at x approximate to 65% as well as the production of a IT' phase along the composition tuning, which are consistent with the experiments. At x = 12.5%, two Mo atoms prefer to form a pair along the Re-4 chains. Gibbs free energy along the reaction path indicates that the best HER performance of nanosheets with 10% Mo originates from the Mo atoms that form Mo-H when there are adjacent Se vacancies.